Psammomatoid juvenile ossifying fibroma of maxilla in a 45-year-old female patient - Sanchita Kundu; Mousumi Pal; Supratim Ghosh; Rudra Prasad Chatterjee (Wolters Kluwer Medknow Publications, 2013)
Juvenile ossifying fibroma (JOF) is an uncommon, benign, yet aggressive fibro-osseous lesion of the jaws commonly occurring in children and young adults and affects equally both males and females. Maxilla is affected more often than mandible. Two microscopically distinct types of JOF, trabecular and psammomatoid varieties have been described, of which latter being more common. A clinical case of psammomatoid variant of JOF (PsJOF) involving the right side of maxilla of a 45-year-old female patient is discussed herewith, encompassing a thorough knowledge of clinical, radiological, and histopathological features.